(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Traditional rice processing techniques retain several advantageous attributes that are often diminished during modern milling operations, potentially offering enhanced suitability for bioplastic production. The present investigation evaluates and compares the physicochemical properties of Traditional Hand-Pounded Rice (THR) and Conventionally Milled Rice (CMR) to determine their effectiveness as raw materials for bioplastic fabrication. The Poongar rice variety was subjected to two processing approaches: traditional hand-pounding and conventional mechanical milling. A detailed characterization was carried out encompassing physical parameters (grain dimensions, density, frictional behavior, and cooking qualities), chemical composition (amylose, amylopectin, and moisture levels), functional properties (water absorption capacity, solubility index, hydration capacity, and swelling power), and micronutrient concentrations (iron, zinc, calcium, and phosphorus). Results revealed that THR exhibited significantly enhanced characteristics, including higher amylose content (28.64 ± 0.92% compared to 24.35 ± 0.84%), improved water absorption capacity (2.48 ± 0.11 g/g versus 2.18 ± 0.09 g/g), increased swelling power (9.32 ± 0.42 g/g versus 8.24 ± 0.35 g/g), and markedly greater micronutrient retention. Additionally, THR demonstrated superior grain integrity, reflected by a lower percentage of broken grains (3.82 ± 0.42% compared to 8.67 ± 0.95%) and higher porosity (60.54 ± 1.85% versus 54.93 ± 1.62%). Overall, traditional hand-pounding effectively preserves key structural and compositional attributes of rice that are advantageous for bioplastic synthesis, particularly elevated amylose levels and improved functional properties that support efficient film formation.